Comparison of the San Francisco Syncope Rule, Canadian Syncope Risk Score and Anatolian Syncope Rule in Patients Presenting to the Emergency Department with Syncope - Doğan, Burcu; Komut, Seval; Sultanoğlu, Hasan; Duran, Cemal Yasin; Yazla, Merve; Günsay, Rabia Handan (The European Research Journal, 2026)
Objectives: Syncope is a common cause of emergency department admissions and poses challenges in patient management due to its broad etiology and risk of short-term adverse events. This study aimed to comparatively evaluate the ability of the San Francisco Syncope Rule, Canadian Syncope Risk Score and Anatolian Syncope Rule to predict short-term (1-week and 1-month) adverse events in patients presenting to the emergency department with syncope. Methods: This multicenter, prospective, observational study included 108 patients who presented to the emergency departments of two tertiary-level hospitals with syncope. Patients aged <18 years, pregnant women, those with non-syncopal causes of transient loss of consciousness, and those requiring hospitalization at presentation were excluded. Patients were contacted by phone on the 7th and 30th days after discharge to assess adverse events, including death, life-threatening arrhythmias, myocardial infarction, aortic dissection, pulmonary embolism, major bleeding, and subarachnoid hemorrhage. Results: The mean age was 45.9±18.9 years, and 57.4% were female. The most common comorbidity was hypertension (34.3%), and vasovagal syncope (47.2%) was the leading etiology. Within 1 week, 8 (7.4%) patients experienced adverse events; none occurred at 1 month. Median scores were 0 for the San Francisco Syncope Rule, 1 for the Anatolian Syncope Rule, and 0 for the Canadian Syncope Risk Score; among those with events: 0.5, 2, 3, respectively. Conclusions: The San Francisco Syncope Rule showed limited early discrimination, the Canadian Syncope Risk Score identified high-risk patients, and the Anatolian Syncope Rule better stratified low–moderate risk groups. Risk scores should complement, not replace, clinical judgment.